Microbiological diagnostic performance of metagenomic next-generation sequencing compared with conventional culture for patients with community-acquired pneumonia - Lin, Tianlai; Tu, Xueliang; Zhao, Jiangman; Huang, Ling; Dai, Xiaodong; Chen, Xiaoling; Xu, Yue; Li, Wushuang; Wang, Yaoyao; Lou, Jingwei; Wu, Shouxin; Zhang, Hongling (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Community acquired pneumonia (CAP) is an extraordinarily heterogeneous illness, both in the range of responsible pathogens and the host response. Metagenomic next-generation sequencing (mNGS) is a promising technology for pathogen detection. However, the clinical application of mNGS for pathogen detection remains challenging. Methods: A total of 205 patients with community acquired pneumonia (CAP) admitted to intensive care unit were recruited, and broncho alveolar lavage fluids (BALFs) from 83 patients, sputum samples from 33 cases, and blood from 89 cases were collected for pathogen detection by mNGS. At the same time, multiple samples of each patient were tested by culture. The diagnostic performance was compared between mNGS and culture for pathogen detection. Results: The positive rate of pathogen detection by mNGS in BALF and sputum samples was 89.2% and 97.0%, which was significantly higher (P<0.001) than that (67.4%) of blood samples. The positive rate of mNGS was significantly higher than that of culture (81.0% vs 56.1%, P=1.052e-07). A group of pathogens including Mycobacterium abscessus (M. abscessus), Chlamydia psittaci, Pneumocystis jirovecii, Orientia tsutsugamushi and all viruses were only detected by mNGS. Based on mNGS results, Escherichia coli was the most common pathogen (15/61, 24.59%) of non-severe patients with CAP, and Mycobacterium tuberculosis (MTB) was the most common pathogen (21/144, 14.58%) leading to severe pneumonia. Pneumocystis jirovecii was the most common pathogen (26.09%) in SCAP patients with immunocompromised status, which was all detected by mNGS only. Conclusion: mNGS has higher overall sensitivity for pathogen detection than culture, BALF and sputum mNGS are more sensitive than blood mNGS. mNGS is a necessary supplement of conventional microbiological tests for pathogen detection of pulmonary infection.